Use of Mulch and Organic Fertilizer on Chrysanthemum - Yohanes Parlindungan Situmeang; I Gusti Made Arjana; Kadek Siliani (Warmadewa University Press, 2017)
This study aims to determine the growth response and yield of chrysanthemum plants in the application of several types of mulch and organic fertilizer. This research uses the basic design of Randomized Block Design with the factorial pattern with 2 factors and 3 replications. The first factor is mulch treatment consisting of 3 levels ie without mulch, rice husk mulch, and black silver plastic mulch. The second factor is organic fertilizer consists of 3 levels namely petrogenic, cow manure and chicken manure. The research results showed that the highest weight of flower stalk was obtained in silver black mulch treatment, increase of 9.63% when compared with the weight of the lowest flower stalk. The highest economic fresh weight was obtained in mulch treatment, increase of 17.53% when compared with the lowest fresh economic weight on mulch rice husk mulch treatment weighing. The highest weight of the flower stalk was obtained in the treatment of cow manure, increased of 10.14% when compared with the lowest weight of the flower stalk obtained in the treatment of cow manure weighing. The highest economic fresh weight was obtained in the cow manure treatment, which increased by 9.91% when compared with the lowest fresh economic interest weight obtained in the treatment of petrogenic fertilizer weighing. Keywords: type mulch, petrogenic, manure; flower